Shared decision-making as a cost-containment strategy: US physician reactions from a cross-sectional survey. Issue 1 (14th January 2014) - Tilburt, Jon C; Wynia, Matthew K; Montori, Victor M; Thorsteinsdottir, Bjorg; Egginton, Jason S; Sheeler, Robert D; Liebow, Mark; Humeniuk, Katherine M; Goold, Susan Dorr
Abstract : Objective: To assess US physicians' attitudes towards using shared decision-making (SDM) to achieve cost containment. Design: Cross-sectional mailed survey. Setting: US medical practice. Participants: 3897 physicians were randomly selected from the AMA Physician Masterfile. Of these, 2556 completed the survey. Main outcome measures: Level of enthusiasm for "Promoting better conversations with patients as a means of lowering healthcare costs"; degree of agreement with "Decision support tools that show costs would be helpful in my practice" and agreement with "should promoting SDM be legislated to control overall healthcare costs". Results: Of 2556 respondents (response rate (RR) 65%), two-thirds (67%) were 'very enthusiastic' about promoting SDM as a means of reducing healthcare costs. Most (70%) agreed decision support tools that show costs would be helpful in their practice, but only 24% agreed with legislating SDM to control costs. Compared with physicians with billing-only compensation, respondents with salary compensation were more likely to strongly agree that decision support tools showing costs would be helpful (OR 1.4; 95% CI 1.1 to 1.7). Primary care physicians (vs surgeons, OR 1.4; 95% CI 1.0 to 1.6) expressed more enthusiasm for SDM being legislated as a means to address healthcare costs. Conclusions: Most US physicians express enthusiasm about using SDM to help contain costs. They believe decision support tools that show costs would be useful. Few agree that SDM should be legislated as a means to control healthcare costs.